Shape instabilities of active epithelial domes under hydraulic stress: Growth, collapse, and oscillation - Dingnan Wu; Xiaosong Guo; Yuehua Yang; Hongyuan Jiang (Proceedings of the National Academy of Sciences, 2026)
Fluid-filled epithelial cavities arise in a wide range of biological contexts, from developmental lumens and embryonic cavities to epithelial domes formed by monolayer delamination. Yet how hydraulic pressure and adhesive rupture coordinate their dynamic shape changes remains poorly understood. Here, using Madin-Darby Canine Kidney (MDCK) epithelial domes as a model system, we combine live imaging with a minimal theoretical model to elucidate the mechanisms governing liquid dome shape dynamics. Our model integrates active ion transport, strain-stiffening tissue mechanics, and cell–cell adhesion rupture-healing kinetics. We identify five distinct dynamic phases: collapse, stable growth, growth-collapse, oscillation, and unbounded growth. These phases emerge from the competition between ion-pumping-induced hydraulic pressure and fracture of cell-substrate and cell–cell adhesions. Crucially, the hydraulic feedback between osmotic influx and rupture-mediated leakage produces self-sustained oscillations akin to stick–slip instabilities in fracture mechanics. Pharmacological experiments further validate the model’s predictions that active ion pumping and adhesion strength control both the observed phase transitions and the characteristics of oscillatory phase. Consistent with the model predictions, measuring the hydrostatic pressure via 3D traction force microscopy reveals that pressure increases with enhanced ion transport and cell-substrate adhesion, but decreases with reduced cell–cell adhesion. These findings establish hydraulic fracture as a central regulator of epithelial dome morphodynamics and suggest a physical mechanism that may contribute to lumen formation and stability in developing tissues.